A study on factors that effect bond price volatility in Malaysia bond market / Nur Hafsah Dan - Dan, Nur Hafsah (2011)
In late 1990s corporate bond plays a significant role in stabilizing financial systems and economic growth. It emerged as an alternative option for acquiring funds from large number of public at the market rate (Nozue, 2007). Bonds consist of paper having a stated amount of coupon rate, maturity time and face value. It is categorized as debt because of its interest feature and superior nature at the time of liquation. The main purpose of this study is to determine the factors that affect the bond price volatility in Malaysia bond market. This study, suggest that the factors are maturity of the bond, market interest rate and yield to maturity of the bond. The study shown that, there are significant relationship between the factors and bond price volatility. The bond price has positive relationship with the maturity and inverse relationships with interest rate and yield to maturity of the bond. Interest rates are found to be the most factors that influence the bond price volatility.